2017
DOI: 10.25115/psye.v6i2.509
|View full text |Cite
|
Sign up to set email alerts
|

Personality and religion among female university students in France

Abstract: ABSTRACT:The short-form Revised Eysenck Personality questionnaire was completed by 462 female university students between the ages of 18 and 30 in France, together with the Francis Scale of Attitude toward Christianity. The findings are consistent with those from a series of studies employing the same measure of religiosity among school pupils and adults in England and Wales, thus adding to the cross-cultural evidence concerning the stability of the association between personality and religion. According to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
3
3
0
Order By: Relevance
“…In terms of personality factors, higher levels of church attendance are significantly correlated with lower psychoticism scores, but independent of both extraversion scores and neuroticism scores. This finding is consistent with the view advanced by Francis (1992) that psychoticism is the dimension of personality fundamental to individual differences in religiosity and supported by a large number of subsequent studies (see Lewis and Francis, 2014). In terms of parental religious identity, high levels of church attendance are significantly correlated with having parents (both mother and father) who are Anglicans, and with having parents (both mother and father) for whom their religious identity is important.…”
Section: Examining Correlationssupporting
confidence: 88%
“…In terms of personality factors, higher levels of church attendance are significantly correlated with lower psychoticism scores, but independent of both extraversion scores and neuroticism scores. This finding is consistent with the view advanced by Francis (1992) that psychoticism is the dimension of personality fundamental to individual differences in religiosity and supported by a large number of subsequent studies (see Lewis and Francis, 2014). In terms of parental religious identity, high levels of church attendance are significantly correlated with having parents (both mother and father) who are Anglicans, and with having parents (both mother and father) for whom their religious identity is important.…”
Section: Examining Correlationssupporting
confidence: 88%
“…In terms of personality factors, higher levels of church attendance are significantly correlated with lower psychoticism scores (r = -.13, p < .001), but independent of extraversion scores (r = .02, ns) and almost independent of neuroticism scores (r = .04, p < .05). This finding is consistent with the view advanced by Francis (1992) that psychoticism is the dimension of personality fundamental to individual differences in religiosity and supported by a large number of subsequent studies (see Lewis & Francis, 2014). In terms of parental religious practice, levels of church attendance are significantly correlated with both mother's (r = .67, p < .001) and father's (r = .54, p < .001) levels of church attendance.…”
Section: Examining Correlations -Insert Table 8 About Here -supporting
confidence: 88%
“…In terms of personality factors, higher levels of church attendance are significantly correlated with lower psychoticism scores, lower extraversion scores, and higher neuroticism scores. The stronger correlation with psychoticism is consistent with the view advanced by Francis (1992) that psychoticism is the dimension of personality fundamental to individual differences in religiosity and supported by a large number of subsequent studies (see Lewis & Francis, 2014).…”
Section: Examining Correlationssupporting
confidence: 84%
“…The first dimension progresses from introversion through ambiversion to extraversion; the second dimension progresses from emotional stability through emotional lability to neurotic disorders; and the third dimension progresses from tendermindedness through toughmindedness to psychotic disorders. In the late 1970s Francis and colleagues began a systematic programme of research to test the connections between these three dimensions and individual differences in religiosity, beginning with studies reported by Kay (1981a, 1981b), Kay (1983a, 1983b), Francis and Pearson (1985a, 1985b concluded from the growing body of evidence that psychoticism was the 'dimension of personality fundamental to religiosity' (p. 645) and subsequent research has tended to confirm that position (for review see Lewis & Francis, 2014).…”
Section: Empirical Perspectivementioning
confidence: 99%